Functional materials for medical and biological purposes on he system CaO-CaF2-P2O5-H2O and additives - Krivileva, S. P.; Moiseev, V. (Scientific and Technological Corporation "Institute for Single Crystals", 2018)
The system of CaO-P2O5 has been studied, he polymorphism of Ca3(PO4)2 has been verified, he position of binary eutectics and the melting points in them on he Ca3(PO4)2-Ca4P2O9 segment have been determined. A diagram of the state of the CaO-P2O5 system is constructed. The experimental verification of the calculated data by the high-temperature microscopy method in sity is performed. The regions of primary crystallization of phases in the system Ca3(PO4)2-CaCO3-Ca(OH)2-H2O are refined. The subsolidus structure of the systems CaO-CaF2-P2O5-H2O and CaO-MgO-CaF2-P2O5 has been studied. The areas promising for the synthesis of materials based on CaO-P2O5-CaF2-H2O system and additives for the reconstruction of structural defects of the skeleton are established.
Функціонвльні матеріали медико-біологічного призначення на основі системи CaO-CaF2-P2O5-H2O і домішок
Keywords: phase diagram; the CaO-P2O5 system; polymorphism; high-temperature microscopy; elementary tetrahedras; correction of skeletal disorders; фазова діаграма; система CaO-P2O5; поліморфізм; високотемпературна мікроскопія; елементарні тетраедри; корекція скелетних порушень